Intra Arterial Heparin Flushing Increases Cereberal Blood Flow in Chronic Ischemic Stroke Patients - Terawan Agus Putranto; Irawan Yusuf; Bachtiar Murtala; Andi Wijaya (The Indonesian Biomedical Journal, 2016)
BACKGROUND: Recently, stroke therapy is focused on reperfusion therapies for restoring cerebral blood flow (CBF) and minimizing the undesired effects of neuron ischemia. However, the thrombolytic therapy to restore CBF was restricted with narrow time window. On other hands, not many patients can reach the treatment immediately after the onset of stroke. A wider time window therapy that might increase CBF would probably helpful. This study aims to investigate the CBF improvement after intra arterial heparin flushing (IAHF) therapy in chronic stroke patients.METHODS: A clinical trial was conducted with time sampling. We collected chronic ischemic stroke subjects (with stroke onset ≥30 days) within periods February-September 2015. We investigated CBF before and after IAHF treatment in 75 chronic stroke patients. The difference before and after IAHF treatment in subgroup which is classified with infarct size and lesion area was tested. CBF was measured using MRI Quality Arterial Spin Labeling (qASL) with region of interest around infarct lesion.RESULTS: We found a significant CBF improvement (p<0.001) around infarct area after IAHF treatment with average 10.39mL/100g/min raised. CBF improvement was found in lacunar infarct (p<0.001) and non lacunar (p<0.001), also in infarct in cortical (p<0.05), subcortical (p<0.001) and both area (p<0.05).CONCLUSION: IAHF is associated with increased CBF around infarct area and IAHF probably offers some benefit for chronic stroke.KEYWORDS: IAHF, CBF, chronic stroke, ischemic, lacunar, non lacunar, cortical lesion, subcortical lesion